The nexus of peer-to-peer lending and monetary policy transmission: Evidence from the People's Republic of China - Nuobu Renzhi; John Beirne (Asian Development Bank (ADB), 2024)
This paper empirically investigates how the level of peer-to-peer (P2P) lending affects monetary policy transmission in the People's Republic of China (PRC). Using statedependent local projection methods, we find that the macroeconomic effects of unanticipated changes in monetary policy are dampened during the boom phase of the P2P lending market. The impulse responses of industrial production and inflation are significantly negative in the non-boom state. In contrast, the responses of industrial production and inflation are muted in the boom state. Set against the context of stricter regulation on P2P lending since 2017, our results indicate that the significant scaling back of P2P lending activity and its gradual decline in the PRC could enhance the effectiveness of monetary policy transmission. Our paper also suggests that further work is needed to study the interaction between financial innovation and monetary policy.
Keywords: E44; E52; F33; F42; 330; peer-to-peer lending; monetary policy transmission; fintech